Changes in contractile protein expression are linked to ventricular stiffness in infants with pulmonary hypertension or right ventricular hypertrophy due to congenital heart disease. Issue 1 (3rd January 2018) - Bond, Andrew R; Iacobazzi, Dominga; Abdul-Ghani, Safa; Ghorbel, Mohammed; Heesom, Kate; Wilson, Mariangela; Gillett, Christopher; George, Sarah J; Caputo, Massimo; Suleiman, Saadeh; Tulloh, Robert M R
Abstract : Background: The right ventricle (RV) is not designed to sustain high pressure leading to failure. There are no current medications to help RV contraction, so further information is required on adaption of the RV to such hypertension. Methods: The Right Ventricle in Children (RVENCH) study assessed infants with congenital heart disease undergoing cardiac surgery with hypertensive RV. Clinical and echocardiographic data were recorded, and samples of RV were taken from matched infants, analysed for proteomics and compared between pathologies and with clinical and echocardiographic outcome data. Results: Those with tetralogy of Fallot (TOF) were significantly more cyanosed than those with ventricular septal defect (median oxygen saturation 83% vs 98%, P=0.0038), had significantly stiffer RV (tricuspid E wave/A wave ratio 1.95 vs 0.84, P=0.009) and had most had restrictive physiology. Gene ontology in TOF, with enrichment analysis, demonstrated significant increase in proteins of contractile mechanisms and those of calmodulin, actin binding and others associated with contractility than inventricular septal defect. Structural proteins were also found to be higher in association with sarcomeric function: Z-disc, M-Band and thin-filament proteins. Remaining proteins associated with actin binding, calcium signalling and myocyte cytoskeletal development. Phosphopeptide enrichment led to higher levels of calcium signalling proteins in TOF. Conclusion: This is the first demonstration that those with an RV, which is stiff and hypertensive in TOF, have a range of altered proteins, often in calcium signalling pathways. Information about these alterations might guide treatment options both in terms of individualised therapy or inotropic support for the Right ventricle when hypertensive due to pulmoanry hypertension or congenital heart disease.